Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 107 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Ceroxylon quindiuense (H.Karst.) H.Wendl.", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 107 records from 12 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002560-150811131857512/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences